2007
DOI: 10.1074/jbc.m611145200
|View full text |Cite
|
Sign up to set email alerts
|

Reticulon 3 Binds the 2C Protein of Enterovirus 71 and Is Required for Viral Replication

Abstract: Enterovirus 71 is an enterovirus of the family Picornaviridae. The 2C protein of poliovirus, a relative of enterovirus 71, is essential for viral replication. The poliovirus 2C protein is associated with host membrane vesicles, which form viral replication complexes where viral RNA synthesis takes place. We have now identified a host-encoded 2C binding protein called reticulon 3, which we found to be associated with the replication complex through direct interaction with the enterovirus 71-encoded 2C protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(135 citation statements)
references
References 43 publications
6
127
0
2
Order By: Relevance
“…45), encapsidation (46), and morphogenesis (47). EV71 2C has been reported to interact with host protein reticulon 3, and thus modulate viral replication (9). In this study, we demonstrate a novel function of 2C protein in modulating TNF-a-mediated NF-kB activation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…45), encapsidation (46), and morphogenesis (47). EV71 2C has been reported to interact with host protein reticulon 3, and thus modulate viral replication (9). In this study, we demonstrate a novel function of 2C protein in modulating TNF-a-mediated NF-kB activation.…”
Section: Discussionmentioning
confidence: 59%
“…The 2C is believed to have two functions during viral RNA synthesis, as follows: as an NTPase and directing replication complexes to cell membranes (8). Recently, EV71 2C protein has been reported to interact with host protein reticulon 3, and this interaction is required for viral replication (9).…”
mentioning
confidence: 99%
“…Heterogeneous nuclear ribonucleoproteins (hnRNPs) are a family of proteins (named hnRNP A1 to hnRNP U) which have RNA-binding and protein-binding motifs. Several hnRNPs, such as A1, C1/C2, E1/E2, I (PTB), and L, are involved in the translational control of cellular or viral mRNAs which contain IRESs (12,31,47,84,100). As noted previously, hnRNP A1 and hnRNP K were found to be associated with the EV71 5ЈUTR and to play essential roles in EV71 replication (51,53).…”
Section: (Iii) Itafsmentioning
confidence: 51%
“…The amino acid sequence of EV71 2C shares 65% similarity with that of poliovirus. Like the 2C protein of PV, EV71 2C plays an important role in forming the viral RNA replication complex by binding to and rearranging mammalian cytoplasmic membranes (84). Using a yeast two-hybrid system to screen a human fetal brain cDNA library, Tang et al (84) demonstrated that RTN 3 interacts with the N-terminal domain of EV71 2C.…”
Section: (Iv) Host Factors Involved In Viralmentioning
confidence: 99%
“…The monoclonal antibody against GAPDH was purchased from Abnova. The polyclonal antibody against 3A (raised against glutathione S-transferase [GST]-3A containing full-length EV71 3A) was described previously (23). The monoclonal antibody against EV71 3D was a gift from Shin-Ru Shih (Chang Gung University, Taoyuan, Taiwan).…”
Section: Silac-msmentioning
confidence: 99%